Respuesta :
Answer:
- x = 1/3
- n = 9
- fourth term = 28/9
Step-by-step explanation:
Given the first three terms of the expansion of (1 +x)^n are 1 +3 +4, you want the values of x and n, and the next term.
Binomial expansion
The first few terms of the binomial expansion of (1 +x)^n are ...
[tex](1+x)^n=1^n+n\cdot1^{n-1}x+\dfrac{n(n-1)}{2}1^{n-2}x^2+\dfrac{n(n-1)(n-2)}{2\cdot3}1^{n-2}x^3+\dots[/tex]
Comparing terms
Comparing the terms to those given, we have ...
[tex]nx=3\\\\(nx)((n-1)x)/2=4[/tex]
Expanding the second of these equations, and substituting the first, we get ...
[tex](nx)(nx -x)=8\qquad\text{multiply by 2}\\\\3(3-x)=8\qquad\text{substitute $nx=3$}\\\\9-8=3x\qquad\text{add $3x-8$}\\\\\boxed{x=\dfrac{1}{3}}\qquad\text{divide by 3}\\\\\dfrac{1}{3}n=3\qquad\text{substitute for $x$ in $nx=3$}\\\\\boxed{n=9}\qquad\text{multiply by 3}[/tex]
Fourth term
Then the fourth term is ...
[tex]\dfrac{n(n-1)(n-2)}{6}x^3=\dfrac{9\cdot8\cdot7}{6}\cdot\left(\dfrac{1}{3}\right)^3=\boxed{\dfrac{28}{9}}[/tex]
__
Additional comment
Then the expansion is ...
(1 +1/3)^9 = 1 + 3 + 4 + 28/9 + 14/9 + 14/27 + ...
The n-th term is (11-n)/(3(n-1)) times the term before.